Porto da Prainha (Santarém-PA): percepções dos usuários - SOUZA, Keuller Santos de (Universidade Federal do Oeste do Pará, 2024)
The port can be understood as a complex place due to the numerous activities that can be carried out in its space. It is an important structure that, at the same time that it can be an item in the transport chain, can serve as infrastructure for numerous cities, which therefore requires greater attention from the Government. In this context, this paper aims to describe the perceptions of users of Porto da Prainha, located in the Prainha neighborhood, in Santarém city, in Pará state. For this, a literature review was carried out on issues inherent to this research object; application of forms to users of this port, interview with one of the representatives of the administrative body of the port, data analysis and, finally, the preparation of this work. Porto da Prainha is relatively new and was built to replace the old Porto da Praça Tiradentes, which was deactivated due to the Orla Project, ending its activities that had been going on for more than twenty years, but in precarious situations. Regarding the users' perceptions, it was observed that despite having a structure considered good, the port already needs improvements in relation to insufficient space for the mooring of vessels and, it was also found that its location is relatively far from commercial establishments, health posts, pharmacies and the like. Because of this, there is dissatisfaction on the part of the interviewed users. However, adjustments are planned in relation to the space destined for berthing.